2012
DOI: 10.1111/j.1467-7652.2012.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Biofortification of plants with altered antioxidant content and composition: genetic engineering strategies

Abstract: email christou@pvcf.udl.es) † These authors contributed equally to this work.Keywords: biofortification, antioxidants, genetic engineering. SummaryAntioxidants are protective molecules that neutralize reactive oxygen species and prevent oxidative damage to cellular components such as membranes, proteins and nucleic acids, therefore reducing the rate of cell death and hence the effects of ageing and ageing-related diseases. The fortification of food with antioxidants represents an overlap between two diverse en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 114 publications
0
72
0
Order By: Relevance
“…To gain insight into all-trans β-carotene accumulation throughout seed development, we determined the accumulation of PSY1 protein (the enzyme that controls the rate-limiting step of carotenoid biosynthesis) by LC-MS/MS at six stages of seed development (10,17,24,30,38, and 45 DAP) in event ABS203-4. We found that PSY1 accumulated to the highest levels at the milkstage (around 17 DAP) and declined sharply to an undetected level at maturity (around 45 DAP) (Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…To gain insight into all-trans β-carotene accumulation throughout seed development, we determined the accumulation of PSY1 protein (the enzyme that controls the rate-limiting step of carotenoid biosynthesis) by LC-MS/MS at six stages of seed development (10,17,24,30,38, and 45 DAP) in event ABS203-4. We found that PSY1 accumulated to the highest levels at the milkstage (around 17 DAP) and declined sharply to an undetected level at maturity (around 45 DAP) (Fig.…”
Section: Significancementioning
confidence: 99%
“…Although sorghum is gluten-free and could be an attractive replacement for wheat-allergy sufferers, it is considered a nutrient-poor crop (8, 9) with very low amounts of β-carotene (10). The improvement of micronutrients in food crops has attracted considerable attention, and significant advances have been made in a range of major crops (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Nutritional improvement in sorghum was undertaken a decade ago (23, 24); however, progress has lagged behind the progress in other crops.…”
mentioning
confidence: 99%
“…Yuan et al (2016) studied the result of enrichment of zinc on antioxidant capacity and growth in pea sprouts and found an increase from 10 to 50 µM Zinc improved antioxidant capacity due in turn to increase the Zn content, chlorophylls, phenolic content and amino acids, Zn enrichment could increase the nutritional quality and antioxidant activity as functional foods. Previous studies showed that the antioxidant capacity may depend on the abundance of metal ions (Zhu et al 2013). This means that certain metals are required in small quantities by humans and they act as cofactors of enzymes, transcription factors and signaling proteins.…”
Section: Antioxidant Capacitymentioning
confidence: 99%
“…Aqueous fluid antioxidants decrease significantly with increasing lenticular nucleus hardness, and reach a minimum at hardness Level V, at which point an ultrasonic emulsification operation is unsuitable (Bonaccio et al, 2013;Zhu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Large amounts of reactive oxygen species accumulate in the aqueous fluid and lenses with age; they cause SOD and GSH-PX consumption, changing the soluble proteins in the lens into insoluble proteins, which results in lens opacity (Lu and Rasco, 2012;Gupta and Ahmad, 2013). Reduced CAT weakens the antioxidant capacity of the lens epithelial cells and induces their apoptosis, which also causes cataracts (Ravipati et al, 2012;Zhu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%